2015
DOI: 10.1002/anie.201500625
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cyclopropyl‐Substituted Furans by Brønsted Acid Promoted Cascade Reactions

Abstract: . (2015) Synthesis of cyclopropyl-substituted furans by Brønsted acid promoted cascade reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…The distinct double bonds (1-2, 5-6) and single bonds (2-3, 4-5) of the reactant equalise in the transition state and localise again into distinct single and double bonds, respectively, in the product. Concomitant cleavage of the cyclopropane bond 3-4 and formation of the new bond between C 1 and C 6 , creates the cycloheptadiene.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The distinct double bonds (1-2, 5-6) and single bonds (2-3, 4-5) of the reactant equalise in the transition state and localise again into distinct single and double bonds, respectively, in the product. Concomitant cleavage of the cyclopropane bond 3-4 and formation of the new bond between C 1 and C 6 , creates the cycloheptadiene.…”
Section: Resultsmentioning
confidence: 99%
“…As part of this programme, we wished to explore whether polycyclic systems containing the cyclohepta[b]furan unit could be synthesised from the cyclopropyl-substituted furans prepared by use of our recently-discovered stereoselective Brønsted acid catalysed cascade reaction (Scheme 1). 6 In previous work, we have shown that treatment of the structurally diverse ynenediones 1 with chloroacetic acid results in intramolecular cyclisation to produce the tricyclic products 2 in which a trisubstituted furan is connected to a cyclopropyl substituent at the α position. The reaction is proposed to occur by carbonyl group protonation, and nucleophilic attack of the oxygen onto the central carbon of the putative allenyl intermediate to produce a carbene that reacts with the pendent alkene to form a cyclopropane.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Clark’s research concerns the development of new synthetic transformations and novel strategies for the total synthesis of complex bioactive natural products. His latest contribution to Angewandte Chemie is a report on Brønsted acid promoted cascade reactions 15…”
Section: Awarded …︁mentioning
confidence: 99%
“…Furan motifs are a common structure pattern found in natural products, pharmaceuticals, and functional materials, and are also served as a building block in organic synthesis . Driven by this prevalence, much attention has been paid to the synthesis of substituted furans to increase their structural diversity and of those that are valuable in medicinal chemistry and drug discovery . Inspite of several well-established general approaches for furan synthesis, metal-catalyzed reactions and organocatalyst-promoted reactions , were reported successively in recent years .…”
Section: Introductionmentioning
confidence: 99%